Policies and teachers’work in the vocational education (Research, Society and Development, 2022)
This article is part of a research and it aims at analyzing how a set of educational policies from the 1990 decade produces meaning effects from official discourses to the vocational educational teachers´ work. The methodological orientation was a qualitative approach of the bibliographic study type. Therefore, it is possible to verify that the hegemonic appeal of current educational policies is that they give better results when they have the direct participation of the Market in their pedagogical, financing and management processes. So, we sought to investigate what has been determining vocational education policies' agenda? Consensus among international Market, school government power, or community participation definition of such? Faced with all conjuncture, the need for greater autonomy on the part of teachers and less control over the participation of the school community in decision-making of those inserted in the educational process is expressed. Finally, it was concluded that an education is one that opens spaces for the democratization of the teaching and learning processes, and it would be a useful lesson to break with current global logic.